2008
DOI: 10.1111/j.1574-6941.2008.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transgenic fructan-producing potatoes on the community structure of rhizosphere and phyllosphere bacteria

Abstract: The rhizosphere and phyllosphere microbial communities of transgenic potatoes producing fructan were studied in comparison with isogenic controls and conventional varieties in a field release experiment over a period of 3 years. Population densities and 16S rRNA gene-based terminal restriction fragment length polymorphism (T-RFLP) analysis of the rhizosphere bacterial community only displayed the influence of annual and seasonal effects and the influence of field heterogeneity. In contrast, the T-RFLP analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
18
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 72 publications
(101 reference statements)
6
18
1
2
Order By: Relevance
“…The high abundance of Acinetobacter sp. in a potato phytosphere has also been reported in a series of previous studies (3, 43, 52). These studies demonstrated that Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 79%
“…The high abundance of Acinetobacter sp. in a potato phytosphere has also been reported in a series of previous studies (3, 43, 52). These studies demonstrated that Acinetobacter spp.…”
Section: Discussionsupporting
confidence: 79%
“…Evaluating these effects in the context of natural cultivar variability showed that changes in the composition of bacterial and fungal communities associated with GM plants were not greater than differences among cultivars. Moreover, the GM effects were negligible compared to the effects of environmental factors, such as field site or year, which were far greater than the effects of genetic modification or plant genotype (2,20,30,38).…”
Section: Discussionmentioning
confidence: 96%
“…However, potential effects of GM plants on microbial communities need to be evaluated in light of natural variation among cultivars of the same plant species. Recently, a study of the rhizosphere communities of fructanproducing GM potatoes compared to those of isogenic controls and conventional cultivars failed to show plant genotype effects (2). However, this result was based only on analysis of Bacteria and did not consider potential effects on different microbial groups.…”
mentioning
confidence: 99%
“…Fortunately, this effect is temporary and its duration is correlated with the duration of γ-lactone assimilation [18,85]. Other changes in the microflora structure have also been recorded [85,89], but they do not appear to be greater than those observed during the phase change associated with plant growth, experimental culture conditions (field and year), climatic variations or cultural practices [56,[109][110][111][112].…”
Section: Discussionmentioning
confidence: 92%